Regioselective and efficient enzymatic synthesis of antimicrobial andrographolide derivatives. Issue 6 (1st April 2018) - Patil, Harshal S.; Jadhav, Dipesh D.; Paul, Ajay; Mulani, Fayaj A.; Karegaonkar, Shrikant J.; Thulasiram, Hirekodathakallu V.
Graphical abstract: Highlights: Efficient enzymatic synthesis of C14-monoester derivatives of andrographolide. Amano lipase mediated efficient esterification of andrographolide. Anti-microbial activity of C14-monoester derivatives of andrographolide. Antimicrobial activity changed with chain length of alkyl group. C14-monoesters of andrographolide exhibited low hemolytic activities. Abstract: Labdane diterpene andrographolide (1 ) is a major constituent of Andrographis paniculata and known to exhibit wide spectrum of biological activities. In this study, regioselective monoesters of (1 ) have been synthesized by using Amano lipase AK ( Pseudomonas fluorescens ) as a biocatalyst. Amano lipase AK was able to execute highly efficient esterification of hydroxyl group attached to C-14 carbon of (1 ) in presence of acyl donors. Among the various synthesized derivatives including two novel compounds such as andrographolide-14-propionate (3 ) and andrographolide-14-caproate (5 ) displayed antimicrobial activity against Staphylococcus aureus with low minimal inhibitory concentration (MIC) 4 µg/mL and 16 µg/mL respectively. Furthermore, they have shown low hemolysis activity at their respective MIC and increase in the permeability of the bacterial cell membrane as delineated by FITC uptake and SEM imaging studies.